Adopsi Teknologi dan Fleksibilitas Manufaktur: Peran Sumber Data sebagai Moderator - Lena Ellitan (Jurnal Manajemen Maranatha, 2005)
Globalization has created an environment where manufacturing organizations must adopt and implement shophisticated technologies (hard technology) and new management practices or techniques (soft technology), if they want to achieve competitive advantage. Shortening product life cycle, increasingly shopisticated customers, increasing labor costs and volatility in input prices has created an environment where manufacturers must be flexible, adaptive, responsive and innovative. Advances Manufacturing Technologies (AMTs) and new management practices provide an organization with an opportunity to successfully compabt market place dynamic and create for itself a competitive advantage. Manufacturers and academics believe that AMTs (hard technology) dan soft technology can improve manufacturing flexibility and lead time to market. This paper is based on an empirical study of one eighty three companies in six industry groups in Indonesia. The main goal of this paper is three folds. Firstly is to document the level of Advanced Manufacturing Technologies (AMTs) and soft technology adoption by Indonesian large manufacturing firms. Secondly is to the effect of technology on manufacturing flexibility. Finnaly is to investigate the moderating role of availability of resources on technology-manufacturing flexibility relationship. This study finds that both hard and soft technology have positive impact on manufacturing flexibility. Furthermore, the availability of resources is found to moderate hard technology-manufacturing flexibility relationship.